2014
DOI: 10.1002/masy.201300196
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Surfactant on the Hydrotalcite Dispersion in NBR/LDH Composites Produced by Coagulation

Abstract: Summary Dispersions of 10% wt hydrotalcite were prepared by mixing using an ultrasound probe and then incorporated into NBR latex for the purpose of evaluating the influence of the surfactant presence and dispersion stability of the hydrotalcite, both in water and in latex. The surfactant used was Pluronic F‐127 and its influence was determined on the size of the agglomerates, the degree of sedimentation and the viscosity of water/LDH dispersions and latex/LDH suspensions. Preliminary results showed the effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…[70b,183] The resulting films display a well‐defined cellular microstructure leading to mechanical percolation behavior and an overall mechanical reinforcement. In a similar approach, nitrile rubber NR/LDH composites were also prepared by latex blending and coagulation . Dispersion stability was ensured by pluronic F‐127 addition acting as a dispersing agent, together with the use of ultrasound in order to decrease particle size and aggregation.…”
Section: Hybrid Ldh Nanocompositesmentioning
confidence: 99%
“…[70b,183] The resulting films display a well‐defined cellular microstructure leading to mechanical percolation behavior and an overall mechanical reinforcement. In a similar approach, nitrile rubber NR/LDH composites were also prepared by latex blending and coagulation . Dispersion stability was ensured by pluronic F‐127 addition acting as a dispersing agent, together with the use of ultrasound in order to decrease particle size and aggregation.…”
Section: Hybrid Ldh Nanocompositesmentioning
confidence: 99%
“…The effect of using the surfactant Pluronic F-127 on the dispersion of Mg-Al LDH in NBR latex was investigated by Braga et al [109]. The LDH adsorbed the hydrophilic groups of the surfactant through hydrogen bonding and the hydrophobic groups of the surfactant then acted as a barrier between LDH particles.…”
Section: Nitrile Butadiene Rubber (Nbr)mentioning
confidence: 99%
“…The four studies in which PU/NBR blends were used were summarised in Table 4 and are repeated here. The study by Braga et al [109] is not summarised here as mechanical property data were not reported. HNBR is made by removing double bonds in the backbone chain of NBR, which makes it more resistant to oxidation than NBR and improves the tensile and tear strength [120].…”
Section: Nitrile Butadiene Rubber (Nbr)mentioning
confidence: 99%
“…In addition, organically modified LDHs can also be applied to rubber composite materials [ 39 ]. NBR has similarly been modified with LDHs to improve its mechanical, thermal and optical properties [ 32 , 40 , 41 , 42 , 43 , 44 , 45 ], with just previous one report on the influence of LDHs on the thermal oxidative aging resistance in NBR materials existing in the literature [ 7 ]. NBR complexes using modified LDHs have also been prepared to improve mechanical properties.…”
Section: Introductionmentioning
confidence: 99%